Analisis Persepsi Mahasiswa Pedidikan Ekonomi tentang Perbankan Syariah: (Studi Kasus Mahasiswa Pendidikan Ekonomi STKIP PGRI Bandar Lampung) - Fitria, Nur (STKIP PGRI Bandar Lampung, 2024)
Syariah banking in Indonesia is currently developing rapidly. The existence of Syariah banks is an alternative for the community besides conventional banks. This research aims to analyze student perceptions about the characteristics, products and services of syariah banking which is a follow-up research on Economic Education students at STKIP PGRI Bandar Lampung. This research on syariah banking is to identify the variables that have the most dominant influence on student perceptions. The population in this study were all Economic Education study program students who had passed the Syariah Economics course and had carried out field observations at syariah banks and financial institutions around the city of Bandar Lampung, totaling 40 people. Data collection instruments in research use questionnaires that have been tested for validity and reliability and are equipped with direct observation and interviews. This research shows the results that the characteristics, products and services of syariah banking have a significant positive effect on students' perceptions of the STKIP PGRI Bandar Lampung Economic Education study program regarding syariah banking, and the characteristics of syariah banking are the variables that most dominantly influence students' perceptions.